2015
DOI: 10.1016/j.jmbbm.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Velocity-based cardiac contractility personalization from images using derivative-free optimization

Abstract: Model personalization is a key aspect for biophysical models to impact clinical practice, and cardiac contractility personalization from medical images is a major step in this direction. Existing gradient-based optimization approaches show promising results of identifying the maximum contractility from images, but the contraction and relaxation rates are not accounted for. A main reason is the limited choices of objective functions when their gradients are required. For complicated cardiac models, analytical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…The contraction parameter in our study was resolved at a high P1 level of resolution. Previous studies have considered contraction parameters that were resolved up to the regional level of AHA zones. By comparing our P1 results to those generated with a regional resolution, we have shown that it is possible to greatly increase the fitting ability of a data assimilation method by increasing the parameter resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contraction parameter in our study was resolved at a high P1 level of resolution. Previous studies have considered contraction parameters that were resolved up to the regional level of AHA zones. By comparing our P1 results to those generated with a regional resolution, we have shown that it is possible to greatly increase the fitting ability of a data assimilation method by increasing the parameter resolution.…”
Section: Discussionmentioning
confidence: 99%
“…The gradients necessary for these optimizations were calculated using direct differentiation or finite difference . More recent efforts include the use of global optimization methods: in particular, genetic algorithms, a Monte Carlo method, subplex algorithm, and parameter sweeps . Finally, reduced order unscented Kalman filtering has also been successfully applied as a data assimilation tool for patient‐specific model creation …”
Section: Introductionmentioning
confidence: 99%
“…These include derivative-free optimization [1], [4], [5], Bayesian estimation by building surrogates using Polynomial chaos [6] or Gaussian process [7], and Bayesian filtering [8]. Essentially, all these methods involve a non-intrusive, repeated evaluation of the physiological model.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is to reduce the dimension of the unknowns by partitioning the cardiac mesh into pre-defined segments and to assume uniform parameter value within each segment. This reduces the spatial field of tissue properties to a low-resolution representation (in the range of 3-26 segments) [1], [4], [7], [11]. As a result of this drastically decreased resolution, the solution has limited ability to reflect different levels of tissue heterogeneity, or the existence of local abnormal tissue with various sizes and distributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation